Thrombin‐PAR1 signaling in pancreatic cancer promotes an immunosuppressive microenvironment. (25th October 2020) - Schweickert, Patrick G.; Yang, Yi; White, Emily E.; Cresswell, Gregory M.; Elzey, Bennett D.; Ratliff, Timothy L.; Arumugam, Paritha; Antoniak, Silvio; Mackman, Nigel; Flick, Matthew J.; Konieczny, Stephen F.
Abstract : Essentials Elimination of PDAC tumor cell PAR1 increased cytotoxic T cells and reduced tumor macrophages. PAR1 KO PDAC cells are preferentially eliminated from growing tumors. Thrombin‐PAR1 signaling in PDAC tumor cells drives an immunosuppressive gene signature. Csf2 and Ptgs2 are thrombin‐PAR1 downstream immune suppressor genes in PDAC tumor cells. Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a prothrombotic state and a lack of host antitumor immune responsiveness. Linking these two key features, we previously demonstrated that tumor‐derived coagulation activity promotes immune evasion. Specifically, thrombin‐protease‐activated receptor‐1 (PAR1) signaling in mouse PDAC cells drives tumor growth by evading cytotoxic CD8a + cells. Methods: Syngeneic mixed cell tumor growth, transcriptional analyses, and functional tests of immunosuppressive response genes were used to identify cellular and molecular immune evasion mechanisms mediated by thrombin‐PAR‐1 signaling in mouse PDAC tumor cells. Results: Elimination of tumor cell PAR1 in syngeneic graft studies increased cytotoxic T lymphocyte (CTL) infiltration and decreased tumor‐associated macrophages in the tumor microenvironment. Co‐injection of PAR1‐expressing and PAR1‐knockout (PAR‐1 KO ) tumor cells into immunocompetent mice resulted in preferential elimination of PAR‐1 KO cells from developing tumors, suggesting that PAR1‐dependent immune evasion is not reliant on CTL exclusion. Transcriptomics analyses revealed no PAR1‐dependent changes in the expression of immune checkpoint proteins and no difference in major histocompatibility complex‐I cell surface expression. Importantly, thrombin‐PAR1 signaling in PDAC cells upregulated genes linked to immunosuppression, including Csf2 and Ptgs2 . Functional analyses confirmed that both Csf2 and Ptgs2 are critical for PDAC syngeneic graft tumor growth and overexpression of each factor partially restored tumor growth of PAR1 KO cells in immunocompetent mice. Conclusions: Our results provide novel insight into the mechanisms of a previously unrecognized pathway coupling coagulation to PDAC immune evasion by identifying PAR1‐dependent changes in the tumor microenvironment, a PAR1‐driven immunosuppressive gene signature, and Csf2 and Ptgs2 as critical PAR1 downstream targets.